Julian Dillon: capstone - Dillon, Julian, artist (Colorado State University. Libraries, 2013)
The artist's statement: My current work explores the idea of painting as a three dimensional setting. As the process developed, I began to incorporate photography, video, and projection with painted objects and space. I term this cross-disciplinary approach "trompe méthode," or "deception of method", as inspired by the historical "trompe l'eoil," or "deception of the eye." These pieces represent domestic settings and behaviors, evoking both universal and personal interpretations of living spaces. The familiarity of the subject matter and the use of sculpture, painting, photography, and video provide various associations of both artistic media and living experience.
Trompe methode
Colorado State University Art Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.